Calcium sulfate: An unconventional bone graft in the management of furcation involvement - A case series - Mukherji Arnav (Wolters Kluwer Medknow Publications, 2019)
This case series is an attempt to evaluate the potentials of calcium sulfate as a regenerative modality in the treatment of furcation involvement. Conventionally, different types of alloplastic bone grafts such as demineralized freeze-dried bone allograft, freeze-dried bone allograft, beta-tricalcium phosphate (β-TCP), hydroxyapatite, bioactive glass, or a combination of these with barrier membrane have been employed. Very few studies have been carried out on human furcation involvement using calcium sulfate bone graft. The results obtained were encouraging in terms of regeneration. This case series sheds light on calcium sulfate in the management of furcal involvement.